Upaya Peningkatan Penguasaan Kosakata Kelas 1 Sekolah Dasar Melalui Papan Flanel Kata Pada Pembelajaran Bahasa Indonesia Materi Keinginan Dan Kebutuhan - M. Reza Azwaldi Zhanni; Donna Boedi Maritasari; Hurun in; M. Syahruddin Amin (FKIP Universitas Khairun, 2025)
The aim of this research is to improve vocabulary mastery using flannel word board media in class I Indonesian language learning at SD Negeri 3 Sekarteja. Based on the researcher's initial observations of class I students at SD Negeri 3 Sekarteja, Selong District, East Lombok Regency, it shows that students' mastery of recognizing the concept of letters and words as a stage of the initial reading process is not in accordance with the stages of development they should be. The low level of students' initial reading mastery was discovered when the teacher carried out an assessment in the process of learning to read words; only 9 out of 29 students were able to read with good criteria. For word mastery, there are criteria that are starting to develop; there are 9 students who can name 4-5 words, while for the criteria that have not yet developed, there are 20 students who have criteria for saying 1-3 words. Looking at the existing problems, initial reading mastery needs to be developed, namely by choosing the right learning media. One medium that can be used to improve vocabulary mastery is using flannel word board media. The subjects of this research were 29 students in class I of SD Negeri 3 Sekarteja, consisting of 16 male students and 13 female students. The method in this research is Kemmis & McTaggart. The actions carried out consist of two (2) cycles. In the first cycle, the post-test results from 29 students increased to 12 students who completed it with a percentage of 41.38. In cycle II the number of results increased to 23 students with a percentage of 79.31%. From the results obtained, it can be concluded that the use of word flannel board media in Indonesian language learning in class I can improve vocabulary mastery.